Biodiversity in Agroecosystems - Collins, Wanda (CRC Press, 2009)
between the diversity of plant and animal species and host/dependent agricultural systems. Biodiversity in Agroecosystems shows how biodiversity can be thought of not only as the rich make-up of a great number of related and competing species within an ecologically defined community, but also as the robust behavior and resilience of those species over time and as the endurance of their eco-community. This book brings to the fore new research on biodiversity in agricultural ecosystems at both micro and macro levels, heretofore available only in journals and proceedings papers.